Simultaneous multielectrode recordings along the human scala tympani: Evidence for level-dependent place coding - Amit Walia; Matthew A. Shew; Shannon M. Lefler; Amanda J. Ortmann; Patrick Ioerger; Jordan Varghese; Jacques A. Herzog; Craig A. Buchman (Proceedings of the National Academy of Sciences, 2026)
The cochlea systematically encodes sound frequency and intensity via a precisely organized tonotopic map, in which traveling waves peak at specific cochlear locations. A fundamental but incompletely understood aspect of auditory coding involves how stimulus intensity shapes this tonotopic organization. In animal models, increasing intensity shifts the cochlear traveling wave peak basally; however, physiological evidence for such intensity-dependent shifts in human cochlear processing is limited. Here, we performed simultaneous multielectrode electrocochleography recordings along the human scala tympani to characterize how cochlear place coding varies as a function of stimulus intensity. In subjects with preserved cochlear mechanics, including individuals with auditory neuropathy spectrum disorder and a subject with normal hearing, we observed pronounced basalward shifts in best-frequency responses of up to ~158° (~one octave) at higher stimulus intensities, along with broader spatial activation. Leveraging the fixed, known distances between electrodes, we quantified cochlear traveling-wave velocity and demonstrated that, although intensity significantly altered spatial activation patterns, the traveling wave’s phase response remained stable across intensities. These results establish physiological evidence that human cochlear frequency representation changes systematically with sound intensity, providing insights into fundamental auditory processing.